2015
DOI: 10.1097/jom.0000000000000383
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Impact of Chronic Health Conditions on Workplace Productivity and Accidents

Abstract: Results suggest that chronic conditions in this workforce are prevalent and costly. Efforts to prevent or reduce condition comorbidity among employees with multiple conditions can significantly reduce costs and workplace accident rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“…An aging workforce has been associated with reduced productivity and increased accident rates [37, 38]. Adverse health conditions affect workplace productivity, through absenteeism, productivity and accidents at DOE National Laboratories [39]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An aging workforce has been associated with reduced productivity and increased accident rates [37, 38]. Adverse health conditions affect workplace productivity, through absenteeism, productivity and accidents at DOE National Laboratories [39]. …”
Section: Resultsmentioning
confidence: 99%
“…There are many contributing factors that affect the risk from exposures, including demographics (age gender), geography, chronic health conditions, and sleep deprivation that may result from shift work [8, 39]. While this paper does not focus on these factors that affect both exposure and risk, some need mentioning, including age, shift work, and level of ecological worker.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ways in which chronic health problems impact one’s experience at work has been explored among groups of workers with specific health conditions such as depression (9), back pain (10), and arthritis (11), and in multiple industries including financial services (12), laboratory sciences (13), and health care (1416). In general, the findings of these studies suggest that as chronic health conditions worsen, an individual’s work experience is adversely affected.…”
Section: Introductionmentioning
confidence: 99%
“…Goetzel et al 11 also found that factors related to high biometric laboratory values (eg, blood pressure), alcohol/tobacco use and emotional problems were associated with higher presenteeism (ie, poor job performance). Frey et al 12 found that some psychosocial factors (eg, poor sleep) were associated with higher presenteeism.…”
Section: Introductionmentioning
confidence: 99%